PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR MATA PELAJARAN IPS DI SDN NOMOR 110 INPRES MATTOMPODALLE DI KABUPATEN TAKALAR - Nurhamdana .; Muh. Yahya; Husain AS (STKIP Pembangunan Indonesia Makassar, 2022)
This study aims to determine: (1) Utilization of the surrounding environment as a learning resource for social studies subjects at SDN No. 110 Inpres Mattopodalle in Takalar Regency; and (2) what are the obstacles that hinder the use of the surrounding environment as a learning resource for social studies subjects at SDN Number 110 Inpres Mattopodalle in Takalar Regency This research is qualitative research with a descriptive approach. The subjects in this study were principals and teachers of SDN Number 110 Inpres Mattompodalle in Takalar Regency. Data collection techniques using interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation and conclusion drawing/verification The results showed that (1) the use of the surrounding environment as a learning resource for social studies subjects at SDN 110 Inpres Mattompodalle, Takalar Regency had never been used by teachers in the implementation of learning. Teachers prefer to teach in the classroom rather than outside the classroom by using a learning resource environment. (2) The constraints on the use of the surrounding environment as a learning resource for students at SDN 110 Inpres Mattopodalle, Takalar Regency were not implemented due to the teacher's preference for teaching in the classroom rather than outside the classroom. Keywords: Environmental Utilization, Learning Resources, Social Studies